Retrospective analysis of endoscopic retrograde cholangio pancreatography (ERCP) procedures in a tertiary care centre in coastal Odisha - Panda, Chitta Ranjan; Das, Haribhakti Seba; Behera, Sambit Kumar; Nath, Preetam (International Journal of Research in Medical Sciences, 2017)
Background: ERCP is commonly performed for radiologic visualisation and therapeutic procedure for treating various pancreatico-biliary disorders. There is no comprehensive data available till date about ERCP procedures from Odisha. The aim of this study was to review the indications and complications of endoscopic retrograde cholangiopancreatography (ERCP) procedures in a tertiary care centre in Odisha. Methods: From July 2013 to December 2016, consecutive patients undergoing ERCP procedure were included in the study. Patients with any previous papillary intervention like papillotomy, sphincterotomy or stent placement were excluded from the study. Patients’ demographic characters, ERCP indications and post-ERCP complications were reviewed. Results: Three hundred and fourteen patients were included in the study. Among them male patients were 161 and females were 153. Mean age was 50.75 years and the age range was 18 to 82 years. Most common indications for ERCP was malignant obstructive jaundice (N = 171, 54%) and choledocholithiasis (N = 137, 43.6%). Post ERCP complications developed in 25 patients (8%). Pancreatitis was the most common post-ERCP complication. Conclusions: ERCP is a safe procedure. ERCP complications in our centre are similar to those reported from other centres.